Determinants of Initial Public Offering (IPO) Underpricing in Malaysian Stock Market - Asri, Marsidi; Fong, Jie We (Human Resource Management Academic Research Society (HRMARS), 2019)
The primary purpose of this study is to examine the effect of issue-specific characteristics and company’s attributes on the existence of underpricing of IPOs listed in Malaysia Stock Exchange from 2012 to 2015. Market-adjusted abnormal return is used as a proxy of dependent variable in this study, namely degree of IPO underpricing whereas the independent variables are the determinants of IPO. This paper aims to illustrates the relationship between the degree of IPO underpricing and the four determinants namely issues price, offer size, company age and market capitalization. Upon the analysis, the degree of IPO underpricing is 21.05% from a sample of 59 IPOs listed in the stock market. By applying multiple regression analysis, noted that market capitalization shows positive relationship with the degree of IPO underpricing whereas issues price and offer size are negatively related to the dependent variable. Moreover, the analysis indicates that the relationship between degree of IPO underpricing and company age is insignificant.